'Just gripping my heart and squeezing': Naming and explaining the emotional experience of receiving bad news in the paediatric oncology setting. Issue 9 (September 2017) - Nelson, Mia; Kelly, Daniel; McAndrew, Rachel; Smith, Pam
Highlights: Recipients' emotional experiences during their bad news consultation were examined. Experiences included bodily sensations, affective states, and cognitive conditions. Experiences related to the news and perceived consequences, more than its delivery. Strong emotional experiences do not necessarily indicate an ineffectual interaction. Abstract: Objective: To explore recipients' perspectives on the range and origins of their emotional experiences during their 'bad news' consultations. Methods: Participants were four bereaved families of children who had changed from active treatment to palliative care in paediatric oncology. Data was collected using emotional touchpoint storytelling. The names (descriptors) given to the emotional experiences were linguistically classified. Explanations of their perceived origins were examined using applied thematic analysis. Results: 26 descriptors were given, relating to bodily sensations, affective states, evaluations and cognitive conditions. Three themes were identified in the origins of these experiences – 'becoming aware', 'the changes' and 'being in this situation'. Parents described strong emotional displays during the consultation including physical collapse. These related to the internal process of 'becoming aware'. Three descriptors were given as originating from the clinicians and their delivery of the news – 'supported', 'included', 'trusting'. Conclusions: Recipients perceive their emotional experiences as mainly originating from the news itself, and perceived consequences of it, rather than its delivery. Strong emotional reactions during the interaction are not necessarily an indicator of ineffectual delivery. Practice Implications: Findings offer a thematic framing that may support and deepen practitioners understanding of recipients' emotional reactions during bad news consultations.